PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DI PASRAMAN PURNA LINGGA PONDOK GEDE BEKASI JAWA BARAT - evi sevriyani, komang; Ayu Suasthi, I Gusti; Gitananda, W.A. Sindhu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Differentiated learning is an effort to adjust the learning process to meet the learning needs of students based on their interests, learning profiles, and readiness. This study aims to analyze differentiated learning implemented in the subject of Hindu Religious Education and Character Education, describe the process of implementing differentiated learning in the subject of Hindu Religious Education and Character Education, and the implications of differentiated learning on students' knowledge, attitudes, and skills in the subject of Hindu Religious Education and Character Education at Pasraman Purna Lingga Pondok Gede Bekasi, West Java. This study uses a descriptive qualitative approach based on constructivism, behaviorism, and social learning theories. Data were collected through observation, interviews, and documentation studies, then analyzed through the stages of data condensation, data presentation, and verification. The results of this study indicate that: (1) differentiated learning is implemented in a structured manner through adjustments to the aspects of context, process, and product according to the level of the students, (2) the learning process is implemented through the stages of opening, core, closing, and evaluation activities, and (3) differentiated learning has positive implications for improving the cognitive, affective, and psychomotor aspects of students. Keywords: Differentiated learning, Pasraman, Hindu Religious Education, Character Education.